2020
DOI: 10.1038/s41588-020-00710-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer therapy shapes the fitness landscape of clonal hematopoiesis

Abstract: Acquired mutations are pervasive across normal tissues. However, our understanding of the processes that drive transformation of certain clones to cancer is limited. Here we study this phenomenon in the context of clonal hematopoiesis (CH) and the development of therapy-related myeloid neoplasms (tMN). We find mutations are selected differentially based on exposures. Mutations in ASXL1 are enriched in current or former smokers, whereas cancer therapy with radiation, platinum and topoisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
475
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 484 publications
(507 citation statements)
references
References 53 publications
24
475
2
6
Order By: Relevance
“…Clinical annotations including age, gender, race, primary cancer diagnosis, length of follow-up, serial blood counts, and smoking history were available for most patients in the study. For 10,375 patients complete treatment data was previously collected 26 . The patients in this study had no record of hematologic malignancies within 3 months following sequencing (Methods).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Clinical annotations including age, gender, race, primary cancer diagnosis, length of follow-up, serial blood counts, and smoking history were available for most patients in the study. For 10,375 patients complete treatment data was previously collected 26 . The patients in this study had no record of hematologic malignancies within 3 months following sequencing (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…10). For a subset of 10,375 patients whose complete clinical treatment history had been previously collected 26 , we explored the association of mCA with receipt of oncologic therapy. We found that mCA was positively associated with external beam radiation therapy (OR = 1.7, P = 0.022) but not cytotoxic chemotherapy (OR = 0.9, P = 0.56) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations